Training on Submitting Articles Through the Open Journal System (OJS) for the Pekanbaru Young Literacy Community: Pelatihan Submit Artikel Melalui Open Journal Sytem (OJS) Bagi Komunitas Literasi Muda Pekanbaru - Fitridawati Soehardi; Lusi Dwi Putri; Winayati Winayati (Yayasan Ahmar Cendekia Indonesia, 2022)
The Ministry of Research, Technology and Higher Education of the Directorate General of Higher Education issued regulation no.44 of 2015 concerning national standards of higher education and a circular letter of the Ministry of Research, Technology and Higher Education of the Directorate General of Learning and Student Affairs no.B 323/B.B1/SE /2019 regarding the publication of scientific works for Undergraduate Programs, Masters Programs and Doctoral Programs. This explains that academic researchers are required to disseminate it by means of seminars, publications, patents or other means so that research results can be known by the general public. In general, the dissemination of scientific works is done online through the Open Journal System. However, with the increase in information technology so that scientific works produced are prone to plagiarism because of the ease of accessing information. The Young Literacy Community is a community consisting of young researchers or final year students who are conducting research and making scientific papers. Partners have a lack of knowledge about how to submit articles through the Open Journal System (OJS). Universities answer partner problems by providing knowledge about the Open Journal System (OJS). The method used is learning in class lectures, discussions and questions and answers as well as practice/simulation applications. The results obtained by participants were able to increase participants' knowledge of the stages of the process of submitting scientific articles through the Open Journal System (OJS) and tricks in overcoming problems when submitting so that participants are expected to be able to implement the knowledge gained in the implementation of publishing results. participant's research work. Abstrak Kementrian Riset, Teknologi, dan Pendidikan Tinggi bagian Direktorat Jendral mengeluarkan peraturan no.44 Tahun 2015 tentang standar nasional pendidikan tinggi dan surat edaran Kementrian Riset, Teknologi, dan Pendidikan Tinggi bagian Direktorat Jendral pembelajaran dan Kemahasiswaan no.B 323/B.B1/SE/2019 tentang publikasi Karya ilmiah Program Sarjana, Program Magister dan Program Doktor. Hal ini menjelaskan bahwa para peneliti akademisi diwajibkan untuk menyebarluaskan dengan cara diseminarkan, dipublikasikan, dipatenkan atau dengan cara lain sehingga hasil penelitian dapat diketahui oleh masyarakat umum. Pada umumnya penyebaran karya ilmiah dilakukan secara online melalui sistem Open Jurnal Sistem. Namun dengan meningkatnya teknologi informasi sehingga karya ilmiah yang dihasilkan rawan terjadinya plagiarisme Karena kemudahan dalam mengakses informasi. Komunitas Literasi Muda merupakan sebuah komunitas yang beranggotakan para peneliti muda atau mahasiswa tingkat akhir yang sedang melakukan penelitian dan membuat karya ilmiah. Mitra memiliki kedala kurangnya pengetahuan tentang cara mensubmite artikel melalui sistem Open Journal Sytem (OJS). Perguruan tinggi menjawab persoalan mitra dengan memberikan pengetahuan tentang sistem Open Journal Sytem (OJS). Metode yang digunakan adalah pembelajaran di kelas ceramah, diskusi dan tanya jawab serta praktik/simulasi aplikasi. Hasil yang diperoleh peserta mampu meningkatkan pengetahuan peserta terhadap tahapan proses mensubmit artikel hasil karya ilmiah melalui Open Journal Sytem (OJS) dan trik-trik dalam mengatasi permasalahan pada saat melakukan submit sehingga diharapkan para peserta dapat mengimplementasikan ilmu yang di dapat dalam pelaksanaan hal melakukan publikasi hasil karya ilmiah penelitian peserta .